2016
DOI: 10.1111/jnc.13498
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of p38 mitogen‐activated protein kinase signaling reduces multidrug transporter activity and anti‐epileptic drug resistance in refractory epileptic rats

Abstract: It is widely recognized that P-glycoprotein (P-gp) mediates drug resistance in refractory epilepsy. However, the molecular mechanism underlying the up-regulation of P-gp expression remains unclear. Our previous studies have demonstrated that p38 mitogen-activated protein kinase (MAPK) regulates P-gp expression in cultured K562 cells. However, a lack of in vivo research leaves unanswered questions regarding whether p38MAPK regulates P-gp expression or drug resistance in refractory epilepsy. This in vivo study e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 47 publications
3
27
0
Order By: Relevance
“…More importantly, P38/JNK signaling pathway was reported to be correlated with epilepsy, which was activated in rat hippocampus postkainic acid‐induced seizure . Besides, in refractory epileptic rats, suppressing p38 signaling weakened multidrug transporter activity and antiepileptic drug resistance . Last but not least, there were no significant alterations after rats accepted injection of miR‐181b agomir and LPS (TLR4 activator).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, P38/JNK signaling pathway was reported to be correlated with epilepsy, which was activated in rat hippocampus postkainic acid‐induced seizure . Besides, in refractory epileptic rats, suppressing p38 signaling weakened multidrug transporter activity and antiepileptic drug resistance . Last but not least, there were no significant alterations after rats accepted injection of miR‐181b agomir and LPS (TLR4 activator).…”
Section: Discussionmentioning
confidence: 99%
“…Potschka's group suggested that inhibition of COX‐2 can attenuate abnormal expression of P‐gp, strengthen brain delivery of AEDs and reduce seizure frequency in epileptic rats . Besides NF‐κB signalling, the p38 MAPK pathway might also be involved in regulating P‐gp expression in refractory epilepsy .…”
Section: Discussionmentioning
confidence: 99%
“…As the axis of several types of signal channels, mitogen-activated protein kinase (MAPK) cascade activation is a key member in the receipt of signals, which are transferred and carried by membrane receptors into the nucleus (6,7), which is key to numerous signaling channels associated with cell proliferation.…”
Section: Introductionmentioning
confidence: 99%